Development of a hot weather warning tool for heat index monitoring in Thailand: 10.55131/jphd/2023/210301 - Paengkaew, Wutthichai; Atsamon Limsakul,; Eakkachai Kokkaew,; Sirapong Sooktawee,; Prachaya Muangnim,; Orasa Naban,; Nidalak Aroonchan,; Aduldech Patpai,; Kittiwan Kitpakornsanti,; Asadorn Kammuang, (Journal of Public Health and Development, 2023)
This study aims to develop and test an extremely hot weather warning tool. The tool consists of a Node MCU ESP8266 microcontroller, air temperature and relative humidity sensor (DHT22), real time clock module (DS3231), micro-SD-card adapter (HW-125), display screen (2004A), and breadboard-shield. It is connected and controlled by Arduino IDE program. Its measurement ranges for temperature, humidity, and heat index are <10 to >50°C, 0 to 100%, and <27 to >50°C, respectively. This device also presents real-time health impacts by displaying one of five warning levels, namely 1) normal level (HI < 27°C), 2) caution level (HI 27°C to <32°C), 3) extreme caution level (HI 32°C to <41°C), 4) danger level (HI 41°C to <54°C), and 5) extreme danger level (HI ≥ 54°C). The data can be directly transferred to a computer by a card adapter. Based on validation with the occupational health and safety standards instrument, no outliers or missing data were found. HIEHT had a highly positive correlation with HIQT36 (r=0.99; p<0.01; n=4,182). Heat Index data measured by this tool was found to have acceptable values with a bias of 0.54 and RMSE of 0.99. For the pilot areas tested, it was found that the extremely hot weather warning tool can fully measure and record, as well as continuously display the results according to the tested date and time. These results show that the developed tool is a simple, easy-to-use, inexpensive, tiny, and portable instrument that can be used to monitor and measure heat to widely communicate extremely hot weather warning information to vulnerable groups and the general public in the community.